Capitalization of Vegetal Wastes for Industrial Application: A Method for Reducing the Associated Pollution and for Increasing the Quality of Life - Radu Claudiu Fierascu; Anda Maria Baroi; Roxana Ioana Matei (Brazdis); Toma Fistos; Irina Fierascu; Alina Ortan; Simona Spinu; Daniela Ionescu (Proceedings, 2023)
Introduction: The recovery of plant waste material is an attractive approach within the framework of EU waste management policies and the development of a circular economy [...]